Effectiveness of Implementation of the One-Door Integrated Service (PTSP) Policy in Improving the Quality of Public Services in Nabire Regency - Fahlevvi, Mohammad Rezza; Tebai, Norlince G (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of the implementation of the One-Stop Integrated Service (PTSP) policy on the quality of public services in Nabire Regency. The background of this study is based on the importance of improving the quality of public services as part of bureaucratic reform, where the PTSP policy is expected to simplify the service process and increase public satisfaction. The method used is a quantitative method with a simple linear regression approach. Data were collected through a questionnaire from 200 respondents who had received services through PTSP. The results of the t-test showed that the implementation of the PTSP policy had a significant effect on the quality of public services with a t-value of 8.083 and a significance of 0.000 (p <0.05). The regression coefficient of 0.594 indicates that every increase in the implementation of the PTSP policy is followed by an increase in the quality of public services. Meanwhile, the R Square value of 0.248 indicates that 24.8% of the variation in the quality of public services can be explained by the implementation of the PTSP policy. This study concludes that the implementation of the PTSP policy effectively contributes to improving the quality of public services in Nabire Regency. Regional governments are advised to continue optimizing the implementation of this policy to support faster, more transparent, and more responsive services to community needs.